2002
DOI: 10.1088/0957-0233/13/8/310
|View full text |Cite
|
Sign up to set email alerts
|

An integrated optical platform for absorptive sensing of chemical concentrations using chemo-optical monolayers

Abstract: In this paper, the design, fabrication and characterization of a sensor is presented, optimized for sensing changes of the absorption coefficient of a monomolecular transduction layer, while at the same time being insensitive to environmental absorption changes. A functional analysis of the device is given, relating the effect of technological uncertainties to systematic errors in the determination of the measurand. A physical implementation of the functional design based on dual mode interrogation, using a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Currently, in our laboratory the converter has been successfully implemented in several integrated optical sensing platforms, such as a fully integrated optical polarimeter [14] and a differential absorption sensor [23]. In these circuits, the converters are used for partial conversion of a launched TE mode into a TM-polarized mode and also for obtaining the interference of TE-and TM-polarized zeroth order modes.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, in our laboratory the converter has been successfully implemented in several integrated optical sensing platforms, such as a fully integrated optical polarimeter [14] and a differential absorption sensor [23]. In these circuits, the converters are used for partial conversion of a launched TE mode into a TM-polarized mode and also for obtaining the interference of TE-and TM-polarized zeroth order modes.…”
Section: Discussionmentioning
confidence: 99%
“…the absorption changes in the sensing layer due to the presence of other (non-specific) chemical species. As a result, serious degradation in the evanescent-wave sensor operation can occur [7]. To overcome this issue, reference waveguides are typically deployed such as in interferometric sensors, in order to distinguish real from spurious sensor response.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that such the absorption changes in the outer medium can be as large as 50 times higher than the absorption changes in the sensing layer due to the presence of other (non-specific) chemical species. As a result, serious degradation in the evanescent-wave sensor operation can occur [7]. To overcome this issue, reference waveguides are typically deployed such as in interferometric sensors, in order to distinguish real from spurious sensor response.…”
Section: Introductionmentioning
confidence: 99%